Pilot Study of Application Status for the Improvement ofWeather Information in the Korean Peninsula: Focus on Extreme Heat Watch and Warnings - Jong-Kil Park; Woo-Sik Jung; Jina Oh; Eun-Byul Kim; Su-Jin Choi (Asian Journal of Atmospheric Environment, 2014)
The extreme heat watch and warnings (EHWW) which is constructed as a part of the climate change adaptation took effect in the summer of 2008, but active response actions failed to be taken because of low perception among citizens. Therefore, a survey investigation targeting citizens residing in Busan and the Gyeongnam province was conducted in order to know the perception regarding EHWW issued by the Korea Meteorological Administration, to identify the main media through which information is acquired, and to propose an improvement measures which may enhance the usefulness and the degree of satisfaction of weather information. The results are as follows; The perception regarding EHWW was not very high as it remained at 59.8% in terms of percentile. Although the statistical significance was not fulfilled in the categories of gender or occupation, significant differences did exist among age groups. The main medium through which citizens acquired information regarding EHWW was the television, which was followed in order by the internet, acquaintances, short message service (SMS), radio, newspapers, the 131 weather hotline, and other media. The usefulness of EHWW was somewhat high (67.2%), and female students were found to utilize the information to a higher degree than male students. The statistics on the level of satisfaction regarding the weather information (65.4%) revealed that most respondents were satisfied. Housewives, professional, and the elder age groups exhibited great satisfaction, leading to the conclusions that the level of perception and interest regarding to the special weather reports (SWR) have an impact on satisfaction of SWR.